Antarctic O3 - Chemical mechanisms for the spring decrease - Mcelroy, Michael B.; Salawitch, Ross J.; Wofsy, Steven C. (1986)
Chemical explanations for the spring decline of Antarctic O3 involve reactions of ClO or interactions between BrO and ClO. Reaction schemes involving Br radicals have the highest efficiency for removal of O3. The chemical mechanisms require low levels of NO(x). Recent cooling of the stratosphere may have triggered formation of HNO3 monohydrate, removing NO(x) and setting the stage for enhanced loss of ozone over Antarctica.